Groteska Pavla Kohouta - Všetička, František (Slavia Occidentalis, 2011)
The text has been devoted to Pavel Kohout’s prose, a Czech prosaist, poet and playwright, one of the most esteemed modern writers. The text focuses on the composition of his literary works, and, first of all, on the way in which the elements of fantasy, grotesque and absurd function in his literature.